The impact of COVID-19 in the elderly and in care homes - Strain, David (Henry Stewart Talks, 2020)
COVID-19 disease outcomes in elderly compared to younger adults, Extent of the problem in the elderly, Other factors contributing to the complications of COVID-19 in care homes, Steps taken by care homes’ staff to mitigate impact of the virus, Steps the home residents can take to help avoid SARS-2 outbreaks, Treatment guidelines for suspected cases, Safety guidelines for care home medical staff and outside visitors